2013
DOI: 10.1159/000351405
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Tadalafil Monotherapy for Lower Urinary Tract Symptoms Secondary to Benign Prostatic Hyperplasia: A Meta-Analysis

Abstract: Objective: To evaluate the efficacy and safety of tadalafil monotherapy for lower urinary tract symptoms secondary to benign prostatic hyperplasia (LUTS/BPH). Methods: A comprehensive search was done to identify randomized controlled trials comparing the efficacy and safety of tadalafil for LUTS/BPH with placebos. Meta-analytical techniques were applied to evaluate the differences in the study results. Results: Eight studies were identified and analyzed. Compared with placebo, tadalafil was associated with sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 3,299 publications
(28 citation statements)
references
References 28 publications
1
24
0
3
Order By: Relevance
“…The interesting article by Dong et al [1] confirmed our data in a systematic appraisal that included exclusively randomized controlled trials based on the high quality of the Jadad score and funnel plot for biases analyses.…”
supporting
confidence: 73%
See 2 more Smart Citations
“…The interesting article by Dong et al [1] confirmed our data in a systematic appraisal that included exclusively randomized controlled trials based on the high quality of the Jadad score and funnel plot for biases analyses.…”
supporting
confidence: 73%
“…The results of the review by Dong et al [1] seem to confirm that aging, metabolic syndrome and hypogonadism could be determinants for the response to daily treatment with tadalafil in men with LUTS due to BPH.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…The responders had an IPSS improvement by ≥5 points, and so they unequivocally experienced a clinically significant symptom relief. According to previous symptom evaluations, a minimum improvement of 3 points is necessary for a patient to perceive a clinical benefit [18,19]. …”
Section: Discussionmentioning
confidence: 99%
“…Several clinical trials have been conducted to investigate the role of PDE5-Is in the LUTS/ED population 9,2426. The main outcomes of these trials have included the effect of therapy on the International Prostate Symptom Score (IPSS) and BPH Impact Index, used to track BPH symptomatology; International Index of Erectile Function (IIEF), reflecting male sexual function; and maximum urinary flow rate (Qmax).…”
Section: Effect Of Pde5-is On Luts/edmentioning
confidence: 99%